Digitalizing interorganizational relationships: Sequential and intertwined decisions for data synchronization. (October 2019) - de Corbière, François; Rowe, Frantz; Saunders, Carol Stoak
Highlights: IOR digitalization as a sequential decision with potentially two interrelated steps. A first decision on the intention to digitalize data exchange between business partners. A second decision on the technology that supports digitalization processes. Combining an extended Sequential Adoption Theory with institutional theory. Adoption factors do not influence similarly each decision. Abstract: Digitalizing interorganizational relationships (IORs) concerns B2B partners adopting and using Interorganizational Information Systems (IOSs). The decision to digitalize IORs involves choices about (1) whether or not to digitalize information flows, and (2) which technology to use. We explore whether these two choices are made sequentially or if they are intertwined. Using sequential adoption theory and institutional theory, we investigate the decisions related to digitalizing IORs through data synchronization. In the context of product information in the French consumer goods and retail industries, analysis of 18 case studies (large firms and SMEs) provides empirical evidence on the distinction between the two related decisions and the factors influencing each one. Our propositions integrate institutional pressures, observational learning, organizational capabilities and technological characteristics.